Informal Employment in Morocco and the Modalities of Employment Flexibility: Econometric Study to Reveal Links That May Exist with Reference to the Cumulative Postulate (American Journal of Economics and Business Innovation, 2025)
This study explores the relationship between informal employment and employment flexibility in Morocco. Informal employment, which accounts for a large proportion of the labor market, is characterized by precarious conditions, lack of job security and absence of social rights. The study focuses on how employment flexibility, which allows companies to adapt contracts and working hours to suit needs, contributes to the expansion of informal employment. It is based on the “cumulative postulate”, which proposes that the accumulation of regulatory and economic changes affects labor informality. Using an econometric approach, the study examines the factors influencing the prevalence of informal employment and shows that increased labor market flexibility, notably through temporary contracts and variable working hours, favors the emergence of informality. This relationship is particularly marked in sectors where labor regulations are less strict, giving companies greater latitude to adjust their workforce without respecting the constraints of formal contracts. The analysis shows that political reforms and economic variations also play a role in this dynamic. The results of the study suggest that to reduce informality, Moroccan authorities should strengthen labor regulations and encourage job formalization while taking into account companies’ need for flexibility. The article concludes that the balance between labor flexibility and the protection of workers’ rights is crucial for sustainable economic development and a fairer labor market while underlining the importance of policies that frame informality to ensure a better quality of life and work for employees.